ANALISIS FAKTOR YANG MEMPENGARUHI CASH HOLDING PADA PERUSAHAAN SEKTOR KONSUMEN PRIMER - Andersson, Morris; Susanti, Merry (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This research was conducted to find out whether cash holding can be influenced by profitability, liquidity, leverage and sales growth. The sample used is a non-cyclical sector company that has consistently been listed on the Indonesia Stock Exchange in the 2019-2021 timeframe. The sample owned was selected using a purposive sampling method and obtained a total of 34 companies. Processing of the data that has been collected uses the multiple linear regression analysis method with SPSS (Statistical Package for the Social Sciences) software version 21. Based on the results of the data that has been processed, it shows that profitability and leverage have a positive and significant effect to cash holding, while liquidity and sales growth has an insignificant effect to cash holding. The implication of this research is for every company to know the importance of the amount of cash held by the company in carrying out the company's activities.